PENGUATAN LITERASI KEBIJAKAN PENDIDIKAN ISLAM BAGI GURU NGAJI DI PESANTREN SALAFIYAH : IMPLEMENTASI MATA KULIAH ANALISIS KEBIJAKAN DALAM PROGRAM PENGABDIAN MASYARAKAT - mubarok, ikhsan; Liqo’ Mursidah; Ainur Rofiq (LPPM STAI Muhammadiyah Probolinggo, 2025)
The transformation of Islamic education in Indonesia cannot be separated from efforts to integrate the values of the pesantren tradition and national education policies. However, one of the main challenges still faced is the low level of policy literacy among Koranic teachers, especially in the salafiyah pesantren environment which still maintains the yellow book-based education pattern. This study aims to strengthen the understanding of Quranic teachers on Islamic education policy through a community service approach based on the Policy Analysis course. The method used was descriptive qualitative, with observation techniques, in-depth interviews, and documentation in island pesantren. The results showed that after attending the training, the Koranic teachers began to be actively involved in local education dialog spaces, such as village education meetings and the sub-district level Indonesian Ulema Council forum. In addition, a synergy between academics and pesantren was also built, creating a participatory and contextual collaboration model. The strengthening of policy literacy is proven to not only improve the Koranic teachers' regulative understanding, but also encourage a change in their role from teaching implementers to strategic actors in community-based Islamic education decision-making. Keywords: policy literacy, Quranic teachers, salafiyah pesantren, community service, academic collaboration